THE RELATIONSHIP BETWEEN SEX, BODY MASS INDEX, DURATION OF USE AND DEVICE SIZE WITH THE OCCURRENCE OF CARPAL TUNNEL SYNDROME - Kurniawan, Jennifer Nathalie; Wardana, I Nyoman Gede; Widianti, I Gusti Ayu; ., Muliani (E-Jurnal Medika Udayana, 2025)
Carpal tunnel syndrome, characterised by wrist pain due to repetitive finger movements, is prevalent among students who frequently use digital devices. This research aims to examine the relationship between sex, body mass index, duration of use, and device size with the prevalence of carpal tunnel syndrome. An observational cross-sectional analytic design was used, which involved 243 Bachelor of Medicine students from Universitas Udayana, batch 2021-2022. These participants were selected using a purposive sampling technique, and all had met the inclusion and exclusion criteria. Data was collected in the form of interviews using questionnaires and analysed using a Chi-Square test with a significance level of a = 0.05. The prevalence of carpal tunnel syndrome is present in 118 (48.6%) respondents, with 83 (70.3%) respondents being female and 35 (29.7%) males. The results of the Chi-Square test showed that there was no significant relationship between the prevalence of carpal tunnel syndrome and sex ( p = 0.193), body mass index (p = 0.699), and device size ( p = 0.052). However, there was a significant relationship between the prevalence of carpal tunnel syndrome and the duration of gadget use ( p = 0.041). This research concludes that the prevalence of carpal tunnel syndrome in students is present in 118 (48.6%) respondents. Furthermore, this research finds that there is a relationship between the occurrence of carpal tunnel syndrome in students and the duration of gadget use. However, there was no relationship between sex, body mass index, device size, and the occurrence of carpal tunnel syndrome.